“Programa Materno Perinatal - Lozano Paima, Hernando (1996)
The Ministry of Health, as Rector of the Technical-Normative Actions for the. Adequate provision of Maternal and Perinatal Health services, has considered formulating the standards in coordination and with the. Participation of the institutions and institutions involved in this type of actions, the Perinatal Maternal Program, a subsidiary body of the Women and Children Program, established by D.S. 002-92-SA of 18.08.92 in fulfillment of its functions to contribute to achieve a significant reduction in maternal perinatal morbidity and mortality., Has considered within its Operative Plan, the standardization for the strengthening and development of activities with Risk criteria that may be adequate according to regional, sub-regional and local reality. In our environment, we are adapting ourselves, that the norms imparted by the governing body, are adapted to our reality since sometimes we encounter certain limitations both materially and economically. That is why the Maternal Perinatal Program must orientate it to the Preventive promotional activities that have the proper reception in terms of the care of the control Pre Natal., Childbirth and Newborn., We must reach the pregnant mother in order to comply with what is stipulated in the program, and in this way reach a happy Term of one. gestation. Standards for maternal perinatal health care and family welfare are necessary for scheduling activities by maternal perinatal health personnel at all levels of the health and maternal health system. The organization of its resources. In view of the foregoing, the present document containing "The Technical Administrative Rules for the Integral Care of Maternal and Perinatal Health" has been elaborated and consists of: General Aspects, comprising of objectives, Scope, Legal basis, Justification And conceptual aspects. Administrative Rules in which are considered the different stages of the process of organization, Planning, Supervision, Evaluation, among others. Technical Standards in which the general guidelines for maternal perinatal health care are indicated. Research standards including guidelines for research proposals at the local level. Educational standards in which guidance is given. The actions of Information Education Communication (IEG) and training. Attached are tables and graphs. In the Department of San Martin, there is an upper house of studies with a Faculty of Obstetrics since the years of its creation, where part of the training of students, carry out activities of projection to the community with a multidisciplinary group (gynecologists, physicians , Obstetricians, etc. and students); The purpose is to emphasize promotion, promotion, prevention, protection and recovery. In reproductive health, teachers, students actively participate to identify health problems in the community and guide us to their line of research and thereby contribute to the solution of their problem. Within this problem the mother-child binomial, although it is true is implementing a series of promotional preventive programs only to serve a group of mothers with appointments, That is to say, those who live in the city and somehow have a facility to be attended by a professional, the problem is serious in the rural and marginal urban areas where they are with medical posts, promoters and lookouts, who do not have the academic training Enough to provide the right service. To the most vulnerable groups. I believe that in order to achieve the objectives proposed, it is necessary to join forces especially with those who have a direct relationship with the remote communities (Mothers' Club, Peasant Organization, etc.) and to carry out training campaigns, counting on teams of professionals who . Miss make to. Marginal urban population. This monograph gives us a detailed view of the Maternal Perinatal Program, which we are sure will contribute to the knowledge of all students of Obstetrics. For later application in the professional performance